The role of the state in Singapore: Pragmatism in pursuit of growth - TAN, Kim Song (Institutional Knowledge at Singapore Management University, 2015)
This paper looks at how government intervention shapes the evolution of the Singapore economy and accounts for its successes and failures over the past 50 years. Compared with other dynamic Asian economies, the Singapore government's approach to intervene in the economy is both more extensive and more intrusive, but with a narrow focus on GDP growth and surplus accumulation as the primary objectives. The ruling government's near complete dominance in politics has enabled it to mobilize resources to create the preconditions for strong GDP growth and high savings. But the impact on the broader development of the economy and the long term sustainability of growth is less obvious. High GDP growth and strong savings have been achieved without developing the inherent production and indigenous innovation capacity, securing a larger hinterland and providing a less skewed income distribution and higher quality of life for residents. As the economy enters a new phase where more complex and multi-faceted development is needed, the Singapore government will require more than its vaunted competency in mobilizing resources to deliver the outcome.